Horsefly (genus Tabanus) bite: allergy or infection?. Issue 2 (7th February 2023) - Kelly, Katherine; Grose, Pauline
Abstract : Summer heatwaves are often associated with increased reports of insect bites as people enjoy spending time outdoors. The horsefly (genus Tabanus), or 'cleg' as it is colloquially known, often receives negative publicity due to peak activity in summer. Following an increase in local hospital presentations due to complications of bites, discussion among colleagues suggested a lack of knowledge regarding best management. We present a case of a woman in her 30s with a large erythematous swelling on her thigh following a suspected horsefly bite. Review revealed no clinical evidence of sepsis but a localised inflammatory response. Inflammatory markers were normal and she was treated with intravenous antibiotics and oral antihistamines to good effect. This case highlights secondary care presentation of a common condition and discusses potential complications, pathogenesis and uncertainties around best practice guidelines for treatment. We highlight strategies to aid antibiotic stewardship, reduce complications and secondary care presentation.